KESALAHAN BERBAHASA DALAM KARANGAN SISWA SEKOLAH DASAR (Sebuah Kajian Berdasarkan Taksonomi Kesalahan Berbahasa) (Language Errors in Students’ Elementary School Essays, An Analysis Based on Three Language Errors Taxonomies) - Achril Zalmansyah (Balai Bahasa Sumatra Barat, 2014)
The problem discussed in this research is language errors in the students’ essays of Class VI SD Al-Kautsar Bandarlampung. This research aimed at to describing the language errors based on three language errors taxonomies. The method used in this research was descriptive it was with using the data sources from students’ essays. Based on the three language errors taxonomies, found that language errors Taxonomy Communicative Effect occupies the biggest mistake with the details of the language errors based Surface Strategy Taxonomy identified in this research found 24 errors (16.12%) from the total 149 errors, which consists of (a) errors in omission found 10 errors, (b) in addition found 11 errors, and (c) on disordering found 3 errors, while (d) in malformation was not found in this research. The language errors based on Comparative Taxonomy identified in this research found 14 errors (9.39%) from the total149 errors, which consists of (a) development found 5 errors, (b) interlingua found 5 errors, and (c) ambiguous found 4 errors, while (d) unique errors in this taxonomy were not found.The language errors based on Communicative Effects Taxonomy identified in this research found 111 errors (74.49%) from the total 149 errors, which consists of global errors found22 errors and local errors found 89 errors .